Through an open window : a novel - Terry, Pamela, 1956- (Ballantine Books, 2025)
"In the small Southern town of Wesleyan, Georgia, where the air smells of red clay and sea salt, Margaret Elliot has lived a seemingly charmed life--until the recent loss of her beloved husband. Since then, Margaret has been seeing visions of her aunt Edith, the indomitable woman who raised her after her parents died when she was a baby. As these mysterious and undeniable visitations continue, Margaret becomes convinced that Aunt Edith is trying to tell her something important. As she follows the clues that almost magically present themselves, it becomes clear there is a secret from Margaret's past waiting to be uncovered. As Margaret grapples with each new revelation, she also worries about her three grown children. Her stoic and inscrutable eldest daughter, Mouse, continues to struggle with the grief of losing her father. Her son Lawrie, always his mother's favorite, faces life-altering changes that he both longs for and fears--while Tom, Lawrie's twin, must wrestle with the consequences of a work decision that has blown up his entire life. Despite the tensions among the siblings as they argue about how best to support their mother, the whole family is soon embroiled in uncovering the truth the ghost of Aunt Edith is striving to expose"-- Provided by publisher.